Ordering Africa : anthropology, European imperialism and the politics of knowledge. - Tilley, Helen; Gordon, Robert J. (Manchester New York : Manchester University Press, 2007)
African research played a major role in transforming the discipline of anthropology in the twentieth century. Ethnographic studies, in turn, had significant effects on the way imperial powers in Africa approached subject peoples.

Ordering Africa provides the first comparative history of these processes. With essays exploring metropolitan research institutes, Africans as ethnographers, the transnational features of knowledge production, and the relationship between anthropology and colonial administration, this volume both consolidates and extends a range of new research questions focusing on the politics of imperial knowledge. Specific chapters examine French West Africa, the Belgian and French Congo, the Anglo-Egyptian Sudan, Italian Northeast Africa, Kenya, and Equatorial Africa (Gabon) as well as developments in Britain, France, Germany, Italy and Switzerland -- Présentation de l'éditeur.
Part I: Metropolitan agendas & institutions -- 1. The elusive bureau of colonial ethnography: African experience and ethnographic terrain in France, 1906–1930 / Sibeud, Emmanuelle -- 2. The advancement of African Studies by the German Research Foundation (GRF), 1920–1945 / Stoecker, Holger -- 3. 'nternationalization and scientific nationalism: the International Institute of African Languages and Cultures (IIALC) Between the Wars'/ Estoile, Benoît de l'. -- Part II: African ethnographers, self-expression, and modernity -- 4. Of conjunctions, comportment, and clothing: the place of African teaching assistants at Hamburg's Colonial Institute, 1909–1919' / Pugach, Sara -- 5. 'Voices of their own?: African participation in the production of colonial knowledge in French West Africa, 1900–1950' / Jezequel, Jean-Hervé -- 6. Custom, modernity and the search for Kihooto: Kenyatta, Malinowski, and the making of facing Mount Kenya / Berman, Bruce; Lonsdale, John -- Part III: Salvage anthropology, primordial imagination, and “Dying races” -- 7. From the Alps to Africa: Swiss missionaries and the rise of anthropology / Patrick Harries -- 8. Colonial Anthropologies and the Primordial imagination in Equatorial Africa / Cinnamon, John -- 9. Colonial medical anthropology and the making of the central African infertility belt / Hunt, Nancy -- Part IV: Colonial states, applied ethnography, and policy -- 10. The scripts of Alberto Pollera, an Italian officer in colonial Eritrea: administration, ethnography and gender / Barbara Sòrgoni -- 11. From political intelligence to colonial anthropology: ethnography in the Sudan intelligence reports and Sudan notes and records / Douglas Johnson -- 12. Colonial ethnology and political rationality in French West Africa / Gary Wilder.
Plusieurs chapitres de ce volume ont été présenté lors d'une conférence à l'université d'Oxford du 10 au 12 mars 2000.
Bibliogr. dissém., index.
0026
Keywords: Ethnology -- Africa; Anthropology -- Africa -- History; Anthropology -- Africa -- Philosophy; Applied anthropology -- Africa; Imperialism